Oxidative stress and HIV infection: target pathways for novel therapies?. (July 2008) - Aquaro, Stefano; Scopelliti, Fernanda; Pollicita, Michela; Perno, Carlo Federico
Oxidative stress is thought to play an important role in the progression of HIV infection. fact, it has been observed that perturbations in antioxidant defense systems, and consequently redox imbalance, are present in many tissues of HIV-infected patients. Moreover, there is clear evidence that oxidative stress may contribute to several aspects of HIV disease, including viral replication, inflammatory response and decreased immune cell proliferation. For this reason, the exogenous supply of antioxidants, as natural compounds and new-generation antioxidants that scavenge free radicals, might represent an important additional strategy for the treatment of HIV infection in the era after HAART therapy has been applied.